Trends and factors affecting in-hospital mortality of patients with pulmonary arterial hypertension - Pandey, Mandvi; Sivakumar, Nithila; Test, Victor (International Journal of Research in Medical Sciences, 2024)
Background: Pulmonary arterial hypertension (PAH) can be fatal without prompt treatment, but targeted therapies have greatly improved life expectancy in the 21st century. Despite these advances, PAH still involves high morbidity and mortality. Over the past decade, new drugs have been approved for PAH, yet research remains limited, and optimal management guidelines are lacking. Methods: This retrospective study used the NIS database from 2016 to 2020 to examine PAH patients. Univariate and multivariate analyses were conducted, adjusting for confounders and Elixhauser comorbidity index was used to assess baseline comorbidity impact. Primary outcomes included mortality trends and factors influencing mortality. Secondary outcomes focused on length of stay and hospitalization charges. Results: PAH admissions increased from 3.8% in 2016 to 30.36% in 2020s. A mortality rate of 6.4% was observed. Despite advancements in therapies, no significant difference in mortality rates was observed during these years. However, total hospitalization charges increased from 2016 to 2020. Age and race significantly influenced mortality. Female gender was associated with lower mortality, while the northeastern and western US had the highest mortality rates compared to the Midwest and South. Uninsured status was linked to higher mortality odds, while obesity had a protective effect. No significant difference in length of stay was noted. Conclusions: This study summarized PAH trends and outcomes from 2016 to 2020, identifying predictive factors for inpatient mortality, length of hospital stays, and treatment costs.